The Economic Sentiment from The Coronavirus Perspective in Indonesia - Khalilur Rahman; Muhammad Basorudin (International Journal of Data Science, Engineering, and Analytics, 2022)
The Coronavirus is becoming a pandemic that gives many impacts not only in the health aspect but also in the social-economics aspect. The Coronavirus spread drastically since the first cases in December 2019. Based on World Health Organization data, the Coronavirus has infected 10,402,389 people and killed 507,000 people all around the world until June 2020. In order to minimize the Coronavirus risk, many countries have adopted strict quarantine policies which impacted on their limited activities including Indonesia. However, this policy made the economy fall down, increased unemployment, and poverty. The Coronavirus has also impacted the national statistics office to collect data directly. As the alternative, big data and sentiment analysis have great potential to become a relevant solution. Sentiment data from online news can be used as supporting data for the economy. By using sentiment analysis, the Indonesia economy and health is in a worrying situation currently. Coronavirus gives negative sentiment for economic factors such as inflation, inflation rate, and composite stock price index (IHSG), high subjectivity index and low polarity index.